Impact of Management Commitment and Safety Culture on Risk Management through Nurse Involvement Intervening - Tati susilawati; Duta Liana; Rina Anindita (International Journal of Health and Social Behavior, 2025)
The Emergency Department (ED) plays a pivotal role as the frontline of hospital services, requiring rapid and accurate response to ensure patient safety and optimal care outcomes. This study aims to analyze the influence of nurse competence and inter-team coordination on the effectiveness of patient transfers from ED to inpatient units, with nurse work motivation as a mediating variable. A quantitative approach was employed with hypothesis testing using path analysis (Structural Equation Modeling - SEM). The study was conducted at Graha Juanda Hospital, Bekasi, involving a sample of 55 nurses selected through total sampling from both the ED and inpatient departments.Primary data were collected through structured questionnaires, and data analysis was performed using SPSS 26 The results demonstrate that nurse competence and team coordination significantly affect service effectiveness, both directly and indirectly through work motivation. The findings also indicate that low work motivation—linked to factors such as limited professional development opportunities and unbalanced workloads—contributes to delays in transferring patients to inpatient care, with the average Length of Stay (LOS) exceeding six hours.The study concludes that improving nurse competence, strengthening inter-team coordination, and enhancing nurse motivation are critical strategies to improve the quality and timeliness of emergency services. This integrated internal performance approach is vital for reducing LOS in the ED and ensuring seamless, patient-centered care transitions.